Monitoring the online antiquarian book trade: the public good and textual heritage in South Korea. Issue 1 (24th June 2020) - de Fremery, Wayne; Kim, Seonghun; Do, Seulki; Han, Sangeun; Oh, Sam G.
Abstract : Purpose: This paper describes a model for integrating publicly available private information concerning textual heritage on the websites of South Korean antiquarian booksellers into the information management systems of the National Library of South Korea (NLK). Design/methodology/approach: A method for formalizing the coproduction of heritage knowledge is presented, using the NLK and textual heritage as a case study. Findings: An investigation of the systems and services of the NLK, interviews with South Korean antiquarian booksellers and the researchers' ability to design a system (including an application profile) that will facilitate the integration of data curated by antiquarian booksellers into the systems of the NLK suggest that it is possible to formalize the coproduction of heritage knowledge. Research limitations/implications: Although this case study is limited to describing the information management procedures of a small number of online South Korean antiquarian booksellers and a single national library, its findings have broad implications. Through discussion of a specific case, the paper identifies a large class of resources that, if acquired, circulated and conserved by public libraries, is likely to enhance the public good provided by public libraries. It also provides an example of how public libraries can better meet their obligations as service and memory institutions by building systems that enable the coproduction of heritage resources by documenting and conserving records related to heritage transactions. Practical implications: The paper demonstrates that it is possible to create a formal system for coproducing heritage information. Social implications: The ability of public libraries to coproduce heritage information is likely to increase the public good provided by public libraries and to make heritage resources more accessible. Originality/value: This paper presents a novel model enabling the curation of publicly available private information about antiquarian texts by a national library to aid cultural understanding and the preservation of documents describing historical texts.